2000
DOI: 10.1073/pnas.180192597
|View full text |Cite
|
Sign up to set email alerts
|

Gel catalysts that switch on and off

Abstract: We report development of a polymer gel with a catalytic activity that can be switched on and off when the solvent composition is changed. The gel consists of two species of monomers. The major component, N-isopropylacrylamide, makes the gel swell and shrink in response to a change in composition of ethanol͞water mixtures. The minor component, vinylimidazole, which is capable of catalysis, is copolymerized into the gel network. The reaction rate for catalytic hydrolysis of p-nitrophenyl caprylate was small when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 19 publications
0
54
0
Order By: Relevance
“…169 The usefulness of such changes was demonstrated by Wang et al, who found that basic vinylimidazole moieties incorporated into a pNIPA gel are more active towards the hydrolysis of pnitrophenyl esters when the gel is in its collapsed, hydrophobic high-temperature state. 170 By contrast, osmium-based complexes tethered to hydrogels of poly(vinylpyridine) were found by Heller et al to undergo electron-transfer reactions less readily after deswelling, because aggregation disfavours the folded conformations needed to bring together neighbouring metal centres. 25 Intuitively, swelling processes should be particularly useful for controlling reactions that are diffusion-limited.…”
Section: Swelling Effectsmentioning
confidence: 98%
“…169 The usefulness of such changes was demonstrated by Wang et al, who found that basic vinylimidazole moieties incorporated into a pNIPA gel are more active towards the hydrolysis of pnitrophenyl esters when the gel is in its collapsed, hydrophobic high-temperature state. 170 By contrast, osmium-based complexes tethered to hydrogels of poly(vinylpyridine) were found by Heller et al to undergo electron-transfer reactions less readily after deswelling, because aggregation disfavours the folded conformations needed to bring together neighbouring metal centres. 25 Intuitively, swelling processes should be particularly useful for controlling reactions that are diffusion-limited.…”
Section: Swelling Effectsmentioning
confidence: 98%
“…Second, reactions that commonly do not proceed well enough in aqueous media may be possible in a hydrogel environment because reactants can be activated through interactions with the hydrogel. Finally, reactants can be concentrated within the hydrogel because of affinity between the reactants and the hydrogel network [63]. Approaches for entrapping man-made catalysts and enzymes in a gel have been investigated and developed since the early Bernfeld and Wan report [64] on physical immobilization of enzymes into a cross-linked synthetic acrylamide gel.…”
Section: Overview Of Gel-based Materials By Applicationmentioning
confidence: 99%
“…A polymer gel can perform some of the fundamental functions of proteins [45,74]. Like proteins, a heteropolymer gel can exist in four thermodynamic phases: (1) Swollen and fluctuating, (2) Shrunken and fluctuating, (3) Shrunken and frozen in a degenerate conformation, and (4) Shrunken and frozen in the global minimum energy conformation.…”
Section: Applications To Imprinted Gel Systemsmentioning
confidence: 99%